Crystal structures of 5-chloro-2-methoxybenzoates of Mn(II), Co(II), Ni(II) and Zn(II) - Stępniak, Krystyna; Ferenc, Wieslawa; Cristóvão, Beata; Lis, Tadeusz (Eclética Química, 2007)
The crystal and molecular structures of [bis(5-chloro-2-methoxybenzoate)tetraaquamanganese(II)], [pentaaqua(5-chloro-2-methoxybenzoato)cobalt(II)] (5-chloro-2-methoxybenzoate), [pentaaqua(5-chloro-2-methoxybenzoato)nickel(II)] (5-chloro-2-methoxybenzoate) and [aquabis(5-chloro-2-methoxybenzoate)zinc(II)] monohydrate were determined by a single-crystal X-ray analysis. Mn(H2O)4L2 (where L = C8H6ClO3) crystallizes in the monoclinic system, space group P21/c. [Co(H2O)5L]L and [Ni(H2O)5L]L both are isostructural, space group P212121. The crystals of [Zn(H2O)L2] H2O are monoclinic, space group Pc. Mn(II) ion is positioned at the crystallographic symmetry center. Mn(II) and Co(II) ions adopt the distorted octahedral coordination but Zn(II) tetrahedral one.The carboxylate groups in the complexes with M(II) cations function as monodentate, bidentate and/or free COO-groups. The ligands exist in the crystals as aquaanions. The complexes of 5-chloro-2-methoxybenzoates with Mn(II), Co(II) and Zn(II) form bilayer structure.